Weather Station - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2022)
Basil, a research supervisor takes students around the weather station of IITA and the purpose of the weather station cannot be overemphasized because, without the information generated from the station, research can not be carried out effectively.https://www.youtube.com/watch?v=fcQ3eEcmYjA